AN ANALYSIS ON A STUDENT’S EXPERIENCE OF USING BLOG AS LEARNING TOOL FOR WRITING ACTIVITY - Andryanus, Andryanus; Regina, Regina; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research concentrates on specific relevant questions, those are how blog helps as learning tool for writing activity and the difficulties of using blog as learning tool for writing activity. Based on the research problem, the design of this research is case study. The subject of this research is one student (Miss X) who has some criteria of having the experiences in using blog, being at least a second semester student(if the student does not have any experience about blog), and having their own blog. The data were collected through interview and observation. From the findings, the researcher finds out that blog helped Miss X learning tool for writing activity by providing a journal or as a media for writing, providing motivational feedback and creating critical thinking environment. The research findings also show that there are some difficulties which faced by Miss X including some difficulties in managing time, lack of Writing skill, programming skill, Multimedia devices, readers and low internet connection.                                                                               Key Words: Analysis, Student?s Experience, Using Blog as Learning Tool, Writing Activity.